Islam and western ethics in science and technology : an analytical study with special emphasis on the Islamic approach - Norunnajjah Ahmat (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study focuses on Islamic ethics, Islamic science and their comparison with Western perspective. This is a qualitative method study that analyses the content of scholarly sources. The study discovered two things. Firstly, the foundation of modern Western ethics and sciences are apparently solid and strong on the outside but fragile inside. Secondly, the Islamic ethics and sciences are founded on a steadfast Tawhidic paradigm but are flexible. Both sides have produced their own worldview of ethics in science and technology. But, which side is the reliable guideline. This study is significant because it proposes five main Qawaid al-Fiqh (Maxims of Islamic Law) as guidelines and principles for developing science and technology. The legal maxim is no stranger to Islamic jurisprudence scholars and can help guide Muslim according to become better. Thus, the same legal maxim could be used to produce ethical practitioners.